Anterior pituitary function in critical illness - Téblick, Arno (Endocr Connect, 2019)
Critical illness is hallmarked by major changes in all hypothalamic–pituitary–peripheral hormonal axes. Extensive animal and human studies have identified a biphasic pattern in circulating pituitary and peripheral hormone levels throughout critical illness by analogy with the fasting state. In the acute phase of critical illness, following a deleterious event, rapid neuroendocrine changes try to direct the human body toward a catabolic state to ensure provision of elementary energy sources, whereas costly anabolic processes are postponed. Thanks to new technologies and improvements in critical care, the majority of patients survive the acute insult and recover within a week. However, an important part of patients admitted to the ICU fail to recover sufficiently, and a prolonged phase of critical illness sets in. This prolonged phase of critical illness is characterized by a uniform suppression of the hypothalamic–pituitary–peripheral hormonal axes. Whereas the alterations in hormonal levels during the first hours and days after the onset of critical illness are evolutionary selected and are likely beneficial for survival, endocrine changes in prolonged critically ill patients could be harmful and may hamper recovery. Most studies investigating the substitution of peripheral hormones or strategies to overcome resistance to anabolic stimuli failed to show benefit for morbidity and mortality. Research on treatment with selected and combined hypothalamic hormones has shown promising results. Well-controlled RCTs to corroborate these findings are needed.